Role of VEGF-A and LRG1 in Abnormal Angiogenesis Associated With Diabetic Nephropathy - Zhang, Afei; Fang, Huawei; Chen, Jie; He, Leyu; Chen, Youwei (Frontiers in Physiology, 2020)
Diabetic nephropathy (DN) is an important public health concern of increasing proportions and the leading cause of end-stage renal disease (ESRD) in diabetic patients. It is one of the most common long-term microvascular complications of diabetes mellitus that is characterized by proteinuria and glomerular structural changes. Angiogenesis has long been considered to contribute to the pathogenesis of DN, whereas the molecular mechanisms of which are barely known. Angiogenic factors associated with angiogenesis are the major candidates to explain the microvascular and pathologic finds of DN. Vascular endothelial growth factor A (VEGF-A), leucine-rich α-2-glycoprotein 1, angiopoietins and vasohibin family signal between the podocytes, endothelium, and mesangium have important roles in the maintenance of renal functions. An appropriate amount of VEGF-A is beneficial to maintaining glomerular structure, while excessive VEGF-A can lead to abnormal angiogenesis. LRG1 is a novel pro-angiogenic factors involved in the abnormal angiogenesis and renal fibrosis in DN. The imbalance of Ang1/Ang2 ratio has a role in leading to glomerular disease. Vasohibin-2 is recently shown to be in diabetes-induced glomerular alterations. This review will focus on current understanding of these angiogenic factors in angiogenesis and pathogenesis associated with the development of DN, with the aim of evaluating the potential of anti-angiogenesis therapy in patients with DN.